Ischemic Stroke in MCA Dissection with the Formation of the Double Lumen: Diagnostic Challenges - Ludmila A. Kalashnikova; Alexey S. Filatov; Marina V. Dreval (Анналы клинической и экспериментальной неврологии)
We describe a patient who experienced a right middle cerebral artery (MCA) stroke at the age of 12. Its clinical manifestations (acute onset of left-sided hemiparesis and headache during swimming) and signs of connective tissue weakness (joint hyperflexibility, increased skin elasticity) suggested right MCA dissection as the stroke cause. However, 1.5T MRI/MRA did not confirm the clinical suspicion: blood flow in the right MCA was preserved, and no intramural hematoma was detected. Only an irregular MCA contour was noted. High-resolution 3T MRI performed seven years later revealed a double lumen in the right MCA — a characteristic dissection sign — confirming the initial clinical hypothesis. This case demonstrates that when MCA dissection is clinically suspected as the cause of ischemic stroke, high-resolution MRI is necessary to verify neuroimaging signs of dissection.